2018
DOI: 10.1007/s10096-018-3203-0
|View full text |Cite
|
Sign up to set email alerts
|

Are animals a source of Stenotrophomonas maltophilia in human infections? Contributions of a nationwide molecular study

Abstract: Stenotrophomonas maltophilia (Sm) is an archetypal environmental opportunistic bacterium responsible for health care-associated infections. The role of animals in human Sm infections is unknown. This study aims to reveal the genetic and phylogenetic relationships between pathogenic strains of Sm, both animal and human, and identify a putative role for animals as a reservoir in human infection. We phenotypically and genotypically characterized 61 Sm strains responsible for animal infections (mainly respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
4
11
1
Order By: Relevance
“…These findings were not only confirmed but also expanded by the MLST scheme proposed by Kaiser et al (20). Since then, several other studies employed the genomic group determination based on the concatenation and alignment of the sequences corresponding to the seven housekeeping genes included in the S. maltophilia MLST scheme as an efficient approach to study the population structure of this pathogen (32)(33)(34). In line with other studies, we also report the predominance of genomic groups 6, 1, and C among our clinical samples, all of which have previously been associated with human sources (20,31).…”
Section: Discussionsupporting
confidence: 86%
“…These findings were not only confirmed but also expanded by the MLST scheme proposed by Kaiser et al (20). Since then, several other studies employed the genomic group determination based on the concatenation and alignment of the sequences corresponding to the seven housekeeping genes included in the S. maltophilia MLST scheme as an efficient approach to study the population structure of this pathogen (32)(33)(34). In line with other studies, we also report the predominance of genomic groups 6, 1, and C among our clinical samples, all of which have previously been associated with human sources (20,31).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, a total of seven isolates were categorized into genogroups 1, 2, 3, or 7 (one or two isolates per genogroup). These findings were different from those of Jayol et al [19], which stated that animal-origin isolates in France were distributed into the main genogroups 2, 5, 6, and 9. Thus, genogroup distribution was likely different across districts and/or animal species.…”
contrasting
confidence: 99%
“…ST501-518 and ST525-529) (Table 1). Such expansive molecular diversity of S. maltophilia was observed in previous studies on animal and human isolates [16,19,20]. Different STs were detected among neighbouring prefectures, except Tokyo and Saitama prefectures (i.e.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Additional studies based on whole-genome sequencing of an increasing number of strains confirmed this phylogenic organization (4)(5)(6). We recently reported the disproportionate representation of some genogroups, not only among human but also among animal infectious strains (7,8). From an epidemiological point of view, animals could be a reservoir for human diseases; while from a phylogenic point of view, animals could constitute an intermediate step for the adaptation of environmental strains to humans.…”
mentioning
confidence: 84%